(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The objective of this research was to assess the effects of extracts of two medicinal plant species: Allium sativum (Linn) and Calotropis procera (Aiton), and a formulation containing azadirachtin on life table parameters of silver leaf whitefly (SLW), Bemisia tabaci biotype B (Gennadius) (Hemiptera: Aleyrodidae), grown on greenhouse tomato plants. The effects were compared to that of pymetrozine, a synthetic insecticide. Bioassays were carried out in a greenhouse under controlled conditions of 27 ± 2ºC, R.H. of 55 ± 5% and 16:8 h (L:D) photo period. All treatments significantly affected the survivorship and fertility of SLW female adults, reducing the net reproduction rate, mean generation time and intrinsic rate of increase of this insect. The net reproductive rate [R0] values for the populations treated with garlic extract, milkweed extract, pymetrozine, azadirachtin, control for extracts (ethanol + distilled water) and control for pesticides (distilled water) were 23.58, 19.32, 10.78, 8.23, 49.66, 57.55; the intrinsic rate of increase [rm] were 0.134, 0.139, 0.110, 0.090, 0.177, 0.178; the mean generation times [T] were 23.49, 21.23, 21.66, 23.50, 22.06, 22.69; the doubling times [DT] were 5.14, 4.95, 6.27, 7.56, 3.91, 3.87, and the finite rates of increase [λ] were 1.144, 1.149, 1.116, 1.094, 1.193, 1.195, respectively. Azadirachtin had the highest effect on the life table parameters of SLW. Our findings indicated that, although herbal extracts were not effective as much as the chemical insecticides, they can be effective in pest control. Therefore, they are suitable choices for replacing chemical insecticides and for alternative use with azadirachtin in SLW IPM program.